Consumer Protection Against the Free Circulation of Blue Label Skincare in the Marketplace: A Sadd Adz-Dzari'ah Perspective - Rama Oktovi; Syafruddin Syam (Program Pascasarjana UIN Sumatera Utara, 2025)
Blue-labeled skincare products freely available in the marketplace pose a serious problem because they contain active ingredients that should only be used under a doctor's prescription and supervision. Without medical supervision, consumers have the potential to experience negative health impacts. This study aims to examine consumer protection for this phenomenon through the Sadd Adz-Dzari'ah approach, namely the principle of prevention in Islamic law to avoid potential damage. As a normative study, the approach used regulations, regulations, and the concept of Sadd Adz-Dzari'ah. Data were collected through the concept of documentary studies and the data were collected and analyzed. Therefore, the results of the study indicate that blue-labeled skincare products are still freely sold in the marketplace and based on the Sadd Adz-Dzari'ah approach, there must be product withdrawal actions or sanctions against business actors who still distribute blue-labeled skincare products and the marketplace must block the store.